POLITIK PENDIDIKAN ISLAM STUDI KEBIJAKAN ORDE BARU TERHADAP MADRASAH - Satria, Rengga (JURNAL PENELITIAN KEISLAMAN, 2014)
A dynamics of Islam education in Indonesia reflects an intense dialectic between Islam educations and the state. Such condition is reflected in some policies made by New Order government, a time when the existence of the Madrasa is determined. This research is qualitative research, descriptive analytic research, with historical approach, and library research as well. Meanwhile data analysis is conducted through: data reduction, data display, drawing calculation and verification (concluding and verification). This research shows that the existence of Madrasa found its new way during the reign of New Order because the government was accommodative upon Islam education especially Madrasa. New Order policies upon Madrasa in general can be drawn into some ways; first, the new order regime tried to bridge education dualism in Indonesia, through togatherly signed decree (SKB) from three ministers in 1975 and confirmed with the 1989 Law of Educational sistem (UUSPN) No. 2. Second, the SKB of three ministers become a starting point to the development of curriculum in Madrasa Education environment. Third, Madrasa education upon the released of common decree of three ministers (SKB Three Minister) is anxiously worried by some people that it could not produce some Islam scholars who are necessary for Islam Ummah. Eventually, the ministry of affairs established MAPK in order to produce Islam Scholars who are able to give a positive response toward National development. Fifth, based on 1989 National Education Sistem No. 2, Madrasa was recognized as public school which emphasized on Islamic nature.